The factors of Lifestyle of Health and Sustainability influencing pro-environmental buying behaviour. (10th October 2019) - Pícha, Kamil; Navrátil, Josef
Abstract: Lifestyle of Health and Sustainability (LOHAS) consumers are seen as environmentally aware, socially attuned and with a view of the world that takes into account personal, community and planetary outcomes. The main aim is to identify the relationship between the consumer's affiliation with a LOHAS segment and its buying behaviour. It is based on a questionnaire survey among costumers of shopping centers. The possibility of identifying the attitude and tendency among the consumers regarding the five factors as defined by the Annual LOHAS Forum was found by confirmatory factor analysis. Three LOHAS segments were found by cluster analysis with rmANOVA test. We have found age and especially gender as important for differentiation of LOHAS market segment. LOHAS consumers could be identified as a group with a specific buying behaviour. Healthy Lifestyles and Ecological Lifestyles correlate strongly in multivariable space (based on redundancy analysis) with the preference for products by companies with similar social values to those of the respondent, the strong interest in socially responsible consumption, and the preference to domestic and local products. Sustainable Economy negatively correlate with influence by marketing, advertisement and sales promotion, impulse buying behaviour, and importance of the price. It is positively correlated with the preference for Fairtrade products. It seems, that LOHAS factors are influenced by East-West paradigm as Personal Development and Alternative Health Care were of low importance for respondents. Graphical abstract: Image 1 Highlights: Three main LOHAS segments were identified – not-interested (34%), partially interested (23%), and interested (43%). Women are more interested in LOHAS than men. The LOHAS customers search for the same values as producers; they prefer local producers, high quality and natural products. There is no single LOHAS segment to target.